Possible relationship among experience, age, income level, gender, and job satisfaction - Hasanzadeh, elham; Gholami , Javad (LPPM Universitas Advent Indonesia, 2023)
Discovering the causes of satisfaction and dissatisfaction is one of the primary goals of job satisfaction studies, and also it has a connection with several important factors. The present study investigates the relationship among Iranian EFL teachers' experience, age, gender, income level, and job satisfaction. To this end, 104 male and female EFL teachers in Urmia, Iran was selected based on convenience sampling design. The participants were asked to fill out an online Job Satisfaction Index (JDI) questionnaire. It evaluates a person in six areas: the nature of the job, supervision, coworkers, promotions, salaries, and benefits, and working conditions. The questionnaires were analyzed by SPSS. In order to investigate the hypothesis, a parametric correlation coefficient was used. The results revealed there was a connection between experience, age, income level, and job satisfaction. However, the gender-job satisfaction connection was determined to be insignificant. It implies that job satisfaction is irrelevant to gender. The implication of the present study can be beneficial to supervisors, institutes, and administrators.